2023
DOI: 10.1158/0008-5472.can-22-3559
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Combination Therapy Enhances Fulvestrant Efficacy and Overcomes Tumor Resistance in ER-Positive Breast Cancer

Abstract: Nanoparticles (NPs) spanning diverse materials and properties have the potential to encapsulate and protect a wide range of therapeutic cargos to increase bioavailability, prevent undesired degradation, and mitigate toxicity. Fulvestrant, a selective estrogen receptor degrader (SERD), is commonly used for treating estrogen receptor (ER)-positive breast cancer patients, but its broad and continual application is limited by poor solubility, invasive muscle administration, and drug resistance. Here, we developed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Li et al 159 developed a bio-compatible micellar nanomedicine, PPFA-cRGD, for targeted co-administration of drugs to tumors to enhance treatment efficacy, abrogate drug tolerance, and reduce side effects. Modifying peptides targeting the NP surface facilitated site-specific drug release, ensuring tissue-specific toxicity to the tumor tissue without affecting healthy tissues.…”
Section: Therapeutic Nps Against Er-positive Bcbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al 159 developed a bio-compatible micellar nanomedicine, PPFA-cRGD, for targeted co-administration of drugs to tumors to enhance treatment efficacy, abrogate drug tolerance, and reduce side effects. Modifying peptides targeting the NP surface facilitated site-specific drug release, ensuring tissue-specific toxicity to the tumor tissue without affecting healthy tissues.…”
Section: Therapeutic Nps Against Er-positive Bcbmmentioning
confidence: 99%
“…This nanomedicine eliminated tumor cells in an in vitro organoid model and in vivo ER-positive BC model. 159 Chittasupho et al 160 demonstrated that encapsulating DOX using a LFC131 peptide-modified polyamidoamine dendrimer led to the targeting and inhibition of CXCR4 on the surface of ER+ BC cells. Paoletti et al 161 proposed an innovative nano-delivery system based on hyaluronic acid involving a biologically active endogenous anionic polysaccharide functionalized with estradiol to produce an amphiphilic derivative, which can form soft NPs or nanohydrogels in water.…”
Section: Therapeutic Nps Against Er-positive Bcbmmentioning
confidence: 99%
“…Moreover, a study revealed that metformin and simvastatin, two metabolism-related drugs, play crucial roles in modulating hypoxic TME and angiogenesis. Furthermore, the combined use of metformin and simvastatin inhibits BC PDO proliferation, promotes apoptosis, alleviates hypoxia, decreases angiogenesis, and enhances vascular normalization (67). Table 3 summarizes the studies on other PDOs.…”
Section: Studies On the Mechanisms Underlying Tumor Progressionmentioning
confidence: 99%
“…Besides, the chemotherapy drugs are mostly cytotoxic drugs, which will cause more serious side effects (Deepak et al., 2023 ; Peña-Corona et al., 2023 ). Therefore, combined administration has attracted more and more attention in anti-tumor research, which can not only reduce the occurrence of drug resistance, improve therapeutic efficacy, but also reduce the incidence of side effects by acting on multiple targets (Li et al., 2023 ; Nguyen et al., 2023 ; Silva et al., 2023 ). Our research group has attempted to combine liver-protective drugs (such as glycyrrhizin, glycyrrhetinic acid, oleanolic acid, diammonium glycyrrhizinate, silymarin, and puerarin) to counteract the toxic effect of ACGs, but no combination has been found that can reduce the toxicity while maintaining the efficacy, and the combination almost invariably significantly reduced the anti-tumor effect of ACGs in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%